Different myocardial microRNA expression patterns are observed in pressure overload- and volume overload-induced chronic heart failure. (14th October 2021) - Ruppert, M; Agg, B; Makkos, A; Sayour, A A; Olah, A; Nagy, D; Balint, T; Paloczi, K; Szenthe, K; Banati, F; Gorbe, A; Ferdinandy, P; et al.
Abstract: Introduction: MicroRNAs (miRNA) are short, single-stranded non-coding RNA molecules that regulate gene expression on the post-transcriptional level. Dysregulation of distinct miRNAs has been found to contribute to the development of chronic heart failure (CHF). However, whether distinct types of CHF are associated with different miRNA expression patterns is debated. Aim: To characterize left ventricular (LV) miRNA expression in rat models of pressure overload (PO) versus volume overload (VO)-induced CHF. Methods: Transverse aortic constriction (TAC) was performed to evoke PO-induced CHF. Aortocaval fistula (ACF) was created to establish VO-induced CHF. Age-matched sham-operated rats served as controls for TAC (ShamT) and ACF (ShamA), respectively. Pressure-volume analysis, echocardiography, histology and quantitative real-time PCR were carried out to assess alterations of the LV. Global miRNA expression profiling was performed using Nanostring technology. Bioinformatics analysis of differentially expressed miRNAs was also carried out to predict relevant miRNA-target interactions. Results: Reduced LV systolic function (ejection fraction: 38±5 vs. 65±2% TAC vs. ShamT, 55±3 vs. 67±3%, ACF vs. ShamA, P<0.01) as well as elevated myocardial B-type natriuretic peptide and increased β-to-α myosin heavy chain gene expression confirmed the development of pathological remodeling and CHF in both models. Nevertheless, characteristic differences could be observed in LV morphology and ultrastructure. Accordingly, the TAC model was associated with robustly increased wall thickness, concentric LV hypertrophy and marked fibrotic remodeling. On the contrary, LV dilatation, eccentric LV hypertrophy and moderate fibrosis were the main morphometric findings in the ACF model. A group of miRNA (rno-miR-130a, 132, 199a-5p, 21, 210, 27b, 326) showed similar alterations in both phenotypes of CHF. However, other miRNAs demonstrated unique (specific to TAC: rno-miR-148b-3p, 150, 199a-3p, 203, 23b, 27b, let-7e; specific to ACF: rno-miR-140, 142-3p, 17-5p, 195, 20a, 204, 214, 27a, 29b, 322, 365, 425, 450a, let-7i) LV expressional changes in distinct phenotypes of CHF. In silico bioinformatics analysis revealed that the altered miRNA expression pattern predominantly controls the cardiac neural crest cell development, the inositol-phosphate pathway and the expression of microtubules-binding proteins. In contrast, alterations in the expression of genes responsible for redox state and epithelial-mesenchymal transition were modified only in the ACF group. Despite of the different signaling cascades, expression of Arhgap12 (Rho GTPase activating protein 12) was predicted to be strongly inhibited in both CHF models. Conclusions: PO and VO-induced CHF are associated with unique miRNA expression patterns, which drive different signaling pathways. miRNA-controlled downregulation of Arhgap12 might represent a common feature in both phenotypes of CHF. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): ÚNKP-20-4-II-SE-20/New National Excellence Program of the Ministry of Human CapacitiesNVKP_16-1–2016-0017 ("National Heart Program") National Research, Development and Innovation Fund of Hungary